A Comparative Study between Screen-Printed and Solid-Contact Electrodes for the Stability-Indicating Determination of Bromazepam - Sherif A. Abdel-Gawad; Ali Altharawi (Molecules, 2022)
Stability-indicating methods are awesome tools to ensure the safety and efficacy of active pharmaceutical ingredients (APIs). An accurate comparative study involving the use of potentiometric sensors for the determination of bromazepam (BRZ) in the presence of its main product of degradation and impurity was performed by the fabrication of two membrane electrodes. A screen-printed electrode (SPE) and a solid-contact glassy carbon electrode (SCE) were fabricated and their performance optimized. The fabricated sensors showed a linear electrochemical response in the concentration range 1.0 × 10−6 M to 1.0 × 10−2 M. The electrodes exhibited Nernstian slopes of 59.70 mV/decade and 58.10 mV/decade for the BRZ-SPE and BRZ-SCE membrane electrodes, respectively. The electrochemical performance was greatly affected by the medium pH. They showed an almost ideal electrochemical performance between pH 3.0 and pH 6.0. The fabricated membranes were applied successfully for the quantification of BRZ in the presence of up to 90% of its degradation product. Moreover, a successful application of the fabricated electrodes was performed for the sensitive and selective quantification of BRZ in its tablet form without any pretreatment procedure.